2021
DOI: 10.2320/matertrans.mt-m2020293
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Observations of the Formation of Surface Fine Crevice Structures Created by Laser Irradiation

Abstract: We used laser irradiation to create surface fine crevice structures, which induced region-selective super-spread wetting. These crevice structures enabled joining of CuCu. We recently reported that laser irradiation can form surface fine crevice structures, not only on Cu but also on Fe surfaces. However, the formation mechanism of such structures is not yet understood. To clarify this mechanism, we performed in situ observations of Cu and Fe surfaces during laser irradiation, with the use of a high-speed came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…The substrate had a surface with a smooth and even structure ( Figure 2 a). Our previous work confirmed that laser irradiation melts the metal and causes swelling and spattering, and as a result, the liquid metal accumulates and forms a fine crevice structure ( Figure 2 b) [ 38 ]. Before the coating process, the fine crevice structure formed on all and 48% of the substrate by laser irradiation ( Figure 2 c,d).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The substrate had a surface with a smooth and even structure ( Figure 2 a). Our previous work confirmed that laser irradiation melts the metal and causes swelling and spattering, and as a result, the liquid metal accumulates and forms a fine crevice structure ( Figure 2 b) [ 38 ]. Before the coating process, the fine crevice structure formed on all and 48% of the substrate by laser irradiation ( Figure 2 c,d).…”
Section: Resultssupporting
confidence: 69%
“…First, a fine structure was formed on the surface to allow liquid copper to spread on the surface. Our previous research confirmed that surfaces with a fine crevice structure can be created by laser irradiation [ 38 ]. As shown in Figure 1 a, a continuous Nd: YAG laser (ML-7062A, Miyachi Corporation, Tokyo, Japan) was used to fabricate the fine crevice structure with two types of patterns: covering all (10 × 10 mm square) and 48% (0.8 mm × 9.9 mm × 6 pcs rectangle arranged at intervals of 1.0 mm) of the substrate, respectively.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation